American Board of Forensic Odontology Standards and Guidelines for Evaluating Bitemarks - Richard Fixott (Taylor & Francis Group, 2023)
ABSTRACTAmerican Board of Forensic Odontology Standards and Guidelines for Evaluating Bitemarks will be reviewed in terms of diagnosis of human bite injuries on skin. ABFO Bitemark Analysis and Comparison Algorithm will be used to discuss application of guidelines. Application of guidelines will be illustrated with case presentations.